A comparative study between covering ileal loop-without ostomy or delayed ostomy and diversion ileostomy for patients undergoing large bowel anastomosis - Sathyaraj P,; Jemin Bharath R,; Renganathan M,; Kalaiselvan N,; Mukesh Kumar P, (Asian Journal of Medical Sciences, 2023)
Background: In elective and emergency general surgery, bowel anastomoses are common procedures. Although several stoma-related issues may arise following stoma creation, establishing a stoma is incredibly morbid. Aims and Objectives: The study compares patients with diversion ileostomies (stomas) to those who had to cover ileal loops without ostomies or delayed ostomies for large bowel anastomosis to compare the risks and advantages of each procedure. Materials and Methods: This prospective and comparative study was conducted on 50 patients undergoing large bowel anastomosis. Patients were divided into two groups: Group A: Those with covering ileal loop without or delayed ostomy, and Group B: Those undergoing diversion ileostomy. Results: Demographic data of the study indicated that most of the participants in both groups were male (72% in covering ileal loop and 64% in diversion ostomy). In both groups, most participants belonged to the >45 age group. We have seen a significant difference in the setting of surgery, Vitamin B 12 levels, early complications, late complications, and time of takedown comparing covering ileal loop to the diversion ostomy group. Conclusion: This study showed reduced postoperative morbidity and complications of stomas following covering ileal loop compared to diversion ileostomy. Hence, the technique should be considered.